Lessons from the reestablishment of Public Health Laboratory activities in Puerto Rico after Hurricane Maria - Margaret C. Hardy; Rita C. Stinnett; Kristine J. Kines; Danisha M. Rivera-Nazario; David E. Lowe; Alexandra M. Mercante; Nathalie Gonzalez Jimenez; Rosa I. Cuevas Ruiz; Héctor I. Rivera Arbolay; Rafael L. Gonzalez Peña; Mayra Toro; Alma A. Trujillo; et al. (Nature Communications, 2019)
Hurricane Maria hit Puerto Rico in 2017 and resulted in a complete loss of activity of the Public Health Laboratories. Here, the authors discuss the approach taken and tools developed to re-establish activity in these laboratories using a quality management system and the lessons learned in this process.